PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP KEMAMPUAN KERJASAMA SISWA KELAS V SD DALAM PEMBELAJARAN MATEMATIKA - Nurul Hikmah; Harry Soeprianto; Lalu Hamdian (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2025)
This study aims to determine the effect of the Cooperative Type Group Investigation learning model to improve the cooperative skills of fifth grade students at SDN 9 Ampenan. This research is motivated by the low ability of student cooperation. Efforts are being made to increase student cooperation by implementing the right learning model, namely by using the Cooperative Type Group Investigation learning model. The subjects of this study were students of class V-A and class V-B SDN 9 Ampenan. This research instrument uses an observation sheet that contains indicators of student cooperation. The data from the student cooperation ability test for the normality test using the Lilifors test in the control class L count = 0.07795 < L table = 0.156624 and the Experiment class, namely the L count = 0.106 < L table = 0.156624, it can be concluded that the data for both classes are normally distributed and the variance is homogeneous. The results showed that there was no difference in the average value of the level of cooperation after being treated between the control class and the experimental class, but there was an increase in the score better than the control class learning that used the usual method or the lecture method